Bacillus cereus AR156-Induced Resistance to Colletotrichum acutatum Is Associated with Priming of Defense Responses in Loquat Fruit - Wang, Xiaoli (PLoS One, 2014)
The effectiveness of a biocontrol agent Bacillus cereus AR156 for control of anthracnose rot caused by Colletotrichum acutatum in harvested loquat fruit and the possible mechanisms of its action have been investigated. Treatment of fruit with B. cereus AR156 resulted in lower disease incidence and smaller lesion diameters compared with that of untreated fruit. The treatment enhanced activities of defense-related enzymes including chitinase, β-1, 3-glucanase, phenylalanine ammonia-lyase, peroxidase and polyphenoloxidase, and promoted accumulation of H(2)O(2). Total phenolic content and 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity were also increased by treatment. Transcripts of three defense-related genes were enhanced only in fruit undergoing both B. cereus AR156 treatment and C. acutatum inoculation compared with those receiving either intervention alone. These results suggest that the disease resistance against C. acutatum in loquat fruit is enhanced by B. cereus AR156 and that the induced resistance is associated with induction and priming of defense responses in the fruit.